Strategi Pemerintah Daerah Kabupaten Karawang dalam Mewujudkan Pendidikan Bermutu Melalui Beasiswa Karawang Cerdas - Okvianti, Delvia; Atthahara, Haura; Noor Azijah, Dewi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2024)
This research aims to determine the strategic management carried out by the Sukaluyu Village This research aims to determine the strategy used by the Karawang Regency Regional Government in implementing the Karawang Cerdas Scholarship Program which started in 2019. The strategy in the Karawang Cerdas Scholarship Program is a benchmark for the results of implementing the program, so it is important to examine a program through a strategy that is used in the policy program. This type of research is research with a qualitative approach and descriptive analysis methods or research that seeks to analyze social life by describing the social world from the perspective or interpretation of individuals (informants) in a scientific setting. The research design in this study is to use an instrumental case study research design to be able to find out and understand the issues and phenomena being studied. The research results show that the strategic management carried out by the Regional Government in the Karawang Cerdas Scholarship Program is based on Fred R. David's strategic management theory, namely 1) strategy formulation; the program has clear objectives and legal basis, 2) strategy implementation; optimizing information distribution by implementing active socialization, 3) strategy evaluation; implementation of new web systems, evaluation of promotional strategies, double checking prospective recipient data. The focus of this research is in Karawang Regency with the focus of research on implementation strategies for the Karawang Cerdas Scholarship Program carried out by the Regional Government of Karawang Regency.